The Role of Digital Religiosity and Consumer Awareness in Ethical Purchasing: A Study on the Global Boycott Movement Against Politically Affiliated Brands - Zulkifli; Juhasdi Susono; Desy Rahmawati Anwar; Akram Ista; Mohd Aderi Che Noh (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
This study aims to examine the influence of religiosity, social media engagement, and product knowledge on consumer participation in boycotts against products affiliated with Israel. Using a quantitative approach and Structural Equation Modeling-Partial Least Squares (SEM-PLS) for data analysis, the research surveyed Muslim consumers to assess how religious values, digital exposure, and awareness drive ethical consumption decisions. The findings demonstrate that religiosity, social media, and product knowledge each have a positive and statistically significant impact on boycott behaviour. These results underscore the increasing significance of faith-driven economic actions, particularly in an era where social media amplifies collective consciousness and mobilization across borders. The implications of this study extend beyond consumer behaviour, reflecting a broader trend in the global Islamic economy, where purchasing choices are increasingly guided by ethical, spiritual, and political considerations. This behaviour fosters a sense of economic solidarity among Muslim communities and reinforces the importance of aligning market actions with Islamic values. For businesses and policymakers, the findings underscore the importance of understanding and responding to the ethical expectations of Muslim consumers. Furthermore, the research encourages consumers to critically evaluate information on social media before making economic decisions, promoting informed activism and reinforcing accountability in global supply chains.